2009
DOI: 10.1016/j.amepre.2009.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Potential Unintended Consequences of Smoke-Free Policies in Public Places on Pregnant Women in China

Abstract: Background Smoke-free policies in public places have become more common in China. Little is known, however, about the potential unintended consequences of such policies on pregnant women. Methods The study was conducted in 2006 in Chengdu, China. Nonsmoking pregnant women (N = 55) whose husband were smokers participated in a study of their knowledge about secondhand smoke and smoke-free policies, their exposure to secondhand smoke, and their husbands’ smoking status at home. This study presents descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…2,22,23,29,[34][35][36][37][38][39][40] Nevertheless, some findings suggest that smoking bans may have negative repercussions. 4,41,42 The relationships between private and public spaces with regard to smoking bans and behavior have been found to be complex and have been said to "demand[] more consideration if interventions in public areas are meant to serve as catalysts for favorable changes in primary private spaces such as homes." 20, p.2 This review aims to determine the overall effect of the enactment of legislative (public) smoking bans or restrictions on voluntary smoking restrictions in private residences as well as to evaluate the current status of the literature and the strength of evidence for and against diffusion and social displacement models.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
See 2 more Smart Citations
“…2,22,23,29,[34][35][36][37][38][39][40] Nevertheless, some findings suggest that smoking bans may have negative repercussions. 4,41,42 The relationships between private and public spaces with regard to smoking bans and behavior have been found to be complex and have been said to "demand[] more consideration if interventions in public areas are meant to serve as catalysts for favorable changes in primary private spaces such as homes." 20, p.2 This review aims to determine the overall effect of the enactment of legislative (public) smoking bans or restrictions on voluntary smoking restrictions in private residences as well as to evaluate the current status of the literature and the strength of evidence for and against diffusion and social displacement models.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
“…In turn, private venues (eg, homes and cars) have generally replaced public spaces as the primary milieu of secondhand smoke (SHS) exposure. [3][4][5][6][7] The objective of this review has been to understand how the enactment of legislative (public) smoking bans or restrictions affect voluntary home smoking bans in private residences.…”
Section: Effects Of Enactment Of Legislative (Public)mentioning
confidence: 99%
See 1 more Smart Citation
“…A study in China found that household SHS exposure increased after smoke-free policies were enacted because smokers shifted their smoking locations from public areas to home (Yao et al, 2009). However, most studies (Akhtar, Currie, Currie, & Haw, 2007;Galan et al, 2007;Haw & Gruer, 2007;Hyland et al, 2008;Ruprecht et al, 2006) have found no evidence of displacement of smoking from public places into the home after implementation of a smoke-free ordinance.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, some studies have found unexpected consequences of a smoke-free policy, especially for disadvantaged populations. These consequences included an increase in SHS at home (Yao, Lee, & Mao, 2009) and a threat to female smokers' safety and public image when smoking on the street (Moore, Annechino, & Lee, 2009). As one part of a national evaluation, our study focused on assessing changes in public awareness and SHS exposure in the workplace and home after media campaigns and a smoke-free ordinance was implemented in Taiwan.…”
Section: Effect Of Media Campaigns and Smoke-freementioning
confidence: 98%